Exosomes: an evolving source of urinary biomarkers and an up-and-coming therapeutic delivery vehicle - Blackwell, Robert H.; Franzen, Carrie A.; Gupta, Gopal N. (Translational Cancer Research, 2017)
Exosomes are a subset of small, extracellular vesicles secreted by all cell types, and can be isolated for virtually all bodily fluids that have been investigated. The importance of exosomal signaling in normal physiology and cancer is clear, with the transfer of host-cell cytoplasmic RNA, intracellular and membrane-bound proteins being well-described.